(untitled) (Annals of Medical Research, 2021)
Aim: The incidence of antenatal hydronephrosis (AHN) has also increased with the raised use of ultrasonography (US); however, there is no consensus on how to approach the babies who were diagnosed prenatally with AHN. The present study aims to investigate the postnatal examination, treatment, and results of babies diagnosed with AHN.Material and Methods: In this study, 276 infants who were followed-up with the diagnosis of AHN between January 2012 and December 2015 in the pediatric nephrology outpatient clinic were evaluated retrospectively. Two hundred and fifty babies with AHN (196 males and 54 females) included in our study. Babies with and without abnormality were compared and etiological causes and treatment modalities of babies with AHN were investigated in the postnatal follow-up.Results: Despite no abnormality detected in 144 (57.6) AHN patients, 106 babies (42.4%) had urinary system abnormality in the postnatal US. As the underlying anomalies, ureteropelvic junction obstruction (UPJO) was the most common in 67 kidneys (63.2%); vesicoureteral reflux (VUR) was found in 29 kidneys (%27.3), ureterovesical junction obstruction (UVJO) in 5 kidneys (4.7%) and posterior urethral valve (PUV) in 3 kidneys (2.8%).Conclusion: Evaluation of babies with AHN starting from postnatal first week will provide early diagnosis of urinary system pathologies and early treatment of babies diagnosed with obstructive pathology.